Plasma Ketone and Medium Chain Fatty Acid Response in Humans Consuming Different Medium Chain Triglycerides During a Metabolic Study Day - St-Pierre, Valérie; Vandenberghe, Camille; Lowry, Carolyne-Mary; Fortier, Mélanie; Castellano, Christian-Alexandre; Wagner, Richard; Cunnane, Stephen C. (Frontiers in Nutrition, 2019)
Background: Medium chain triglycerides (MCT) are ketogenic but the relationship between the change in plasma ketones and the change plasma medium chain fatty acids (MCFA) - octanoate, decanoate, or dodecanoate – after an oral dose of MCT is not well-known. An 8 hour metabolic study day is a suitable model to assess the acute effects on plasma ketones and MCFA after a dose of tricaprylin (C8), tricaprin (C10), or trilaurin (C12) or mixed MCT (C8C10). Objective: To assess in healthy humans the relationship between the change in plasma ketones, and octanoate, decanoate and dodecanoate in plasma total lipids during an 8 hour metabolic study day in which a first 20 ml dose of the homogenized test oil is taken with breakfast and a second 20 ml dose is taken 4 hours later without an accompanying meal. Results: The change in plasma acetoacetate, β-hydroxybutyrate and total ketones was highest after C8 (0.5 to 3 h post-dose) and was lower during tests in which octanoate was absent or was diluted by C10 in the test oil. The plasma ketone response was also about two fold higher without an accompanying meal (P=0.012). However, except during the pure C10 test, the response of octanoate, decanoate or dodecanoate in plasma total lipids to the test oils was not affected by consuming an accompanying meal. Except on C12, the 4 h area-under-the-curve of plasma β-hydroxybutyrate/acetoacetate was 2-3 fold higher when no meal was consumed (P<0.04). Conclusion: C8 was about three times more ketogenic than C10 and about six times more ketogenic than C12 under these acute metabolic test conditions, an effect related to the post-dose increase in octanoate in plasma total lipids.